Effect of the application of high power ultrasonic waves (25khz) on physicochemical and microbiological properties of semitendinosus longissimus muscle of bovine species: Effect of Ultrasound on the physicochemical and Microbiological properties Of A Muscle Of Bovine Species (Revista de Investigaciones Universidad del Quindío, 2016)
Application of high power ultrasound, as a non-chemical technology, to improve the quality and safety of meat was studied, evaluating the effects of ultrasonic waves on physicochemical (pH, ash, acidity, water activity, moisture, water holding capacity) and microbiological properties (aerobic mesophilic bacteria, total and fecal coliforms) of a semitendinosus muscle Longissimus in male animals between 4 and 5 years old, which had 12 hours post-mortem. For the study, the samples were worked independently and in triplicate whith ultrasound treatment at a frequency of 25 kHz, for exposure times of 30, 45 and 60 minutes. The results were analyzed using commercial software SPSS version 11.0, by computing analysis of variance (ANOVA) with completely randomized design and signifi cant difference least α = 0.05. These results showed that after the ultrasound treatment, properties such as pH, water holding capacity (WHC), ashes, acidity and water activity (ɑw) do not have statistically signifi cant changes (α = 0.05) by ANOVA, which evidence that treatment does not affect the quality of meat; other hand, muscle moisture presents a signifi cant decline (α = 0.05) due to cavitation caused by the ultrasound waves which generates micro water evaporation, the effects on the microbial load infl uences a decreasing on aerobic mesophilic, total and fecal coliforms on muscle reaching a microbial inactivation with favorable results after exposure periods of 60 minutes.
Keywords: Wather holding capacity; Water activity; ashes; pH; frequency; ultrasound; food safety